Coaches' Feedback Quality and Skill Development of Badminton Athletes in an Institute of Technology in Jiangxi Province, China - Wang, Hezhuang (Pacific International Journal, 2025)
This study investigates the relationship between coaches’ feedback quality and the skill development of badminton athletes at the Nanchang Institute of Technology in Jiangxi Province, China. Utilizing a descriptive-comparative-correlational design, 304 badminton athletes were surveyed on their demographic profiles, their assessment of their coaches’ feedback quality (across dimensions of relevance, clarity, timing, and tactical insight), and their self-assessment of their own skill development following feedback sessions. Results indicated that athletes perceived their coaches' feedback as constructive overall. Furthermore, athletes reported significant improvements in their skills, particularly in self-monitoring and tactical application, after receiving feedback. While no significant differences were found in these perceptions based on demographic factors (age, sex, years of experience), the study concludes that high-quality, well-communicated feedback is a critical component of athlete development. The findings support the implementation of programs to further enhance coaches' feedback delivery techniques.